Assessing Infrastructure Development in Kedungrejo Village Work Plan - Agustina, Isna Fitria; Felani, Herman (Indonesian Journal of Public Policy Review, 2024)
Background: Effective policy implementation is essential for achieving developmental goals, particularly in rural areas. Specific Background: This study examines the implementation of the Government Work Plan (RKP) in Kedungrejo, Jabon District, Sidoarjo. Knowledge Gap: There is limited research on the operational challenges of RKP implementation in rural Indonesia. Aims: The research analyzes RKP implementation, focusing on communication, resources, disposition, and bureaucratic structure per Edward III’s framework. Results: Findings reveal that village officials engage in monitoring infrastructure projects but lack Standard Operating Procedures (SOPs) and dedicated oversight teams. Novelty: This study offers empirical insights into the practical challenges faced in RKP implementation. Implications: Establishing SOPs and dedicated teams is recommended to improve coordination and accountability, enhancing governance and community participation in rural development efforts. Highlights : Lack of SOPs: Absence of Standard Operating Procedures hinders effective project oversight. Community Engagement: Village officials emphasize the importance of involving the community in development efforts. Bureaucratic Structure: The existing bureaucratic framework influences the coordination and success of RKP implementation. Keywords: RKP, rural development, governance, implementation, community participation